PERSEPSI DAN PERILAKU MASYARAKAT TERHADAP ORANG DENGAN GANGGUAN JIWA : STUDI KUALITATIF - Brigita Saluhang; Andi Buanasari; Ferdinand Wowiling; Hendro Bidjuni (JURNAL KEPERAWATAN, 2022)
Background The number of people with mental disorders based on data from the Talaud Islands District Health Office in 2019 was 212 people with mental disorders spread over 15 sub-district out of 19 sub-district. In Indonesia, there are still many inappropriate ways to treat people with mental disorders, for example, wrong behavior and public perception, and high stigma and continues to grow in the community. The purpose of this research is to get an overview of the public’s perception and behavior towards people with mental disorders in Rarange Village Kabaruan District Talaud Islands Regency. This method study uses qualitative research methods with a phenomenological approach. Sampling in this study uses a purposive sampling method involving thirteen participants. Data analysis was used based on the Colaizzi method. The results of the study obtained four themes that are public perceptions related factors that cause mental disorders, negative public perception of people with mental disorders, positive public perception of people with mental disorders, and community behavior towards people with mental disorders. The conclusion is that the public perception and behavior can make an impact on people with mental disorders depending on the good and bad perceptions and behaviors given by the community. Stigma is not only felt by people with mental disorders but also by their families. The public must be educated to better understand mental disorders.